Hermeneutics, Scriptural Politics, and Human Rights
XIII, 277 p.
Keywords: This book articulates the relationships involving hermeneutics and scriptural politics in the complex fields of religious freedom and human rights, with particular focus on women and minorities in Christianity, Judaism, and Islam.